2019
DOI: 10.1007/s40477-019-00382-5
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of intrapartum ultrasound by mothers in an African population

Abstract: Introduction Intrapartum ultrasound is gaining high acceptance by many women as another method for assessing labour progression. Despite growing evidence of the effectiveness of ultrasound in labour, the acceptance of intrapartum ultrasound has not been previously investigated in black Africans. Aim This study aimed to determine women's acceptance of intrapartum ultrasound and their preference for transperineal ultrasound or digital vaginal examination (digital VE) in Ghana. Methods An analytical cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In this study, TPUS was done in a short time with less discomfort to the pregnant ladies as reported by all of the participants compared with the digital vaginal examination. Only few previous studies support this finding [12,17,21].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In this study, TPUS was done in a short time with less discomfort to the pregnant ladies as reported by all of the participants compared with the digital vaginal examination. Only few previous studies support this finding [12,17,21].…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, various studies claimed that using digital pelvic examination during labor is inaccurate and misleading regarding deciding the mode of delivery. Misinterpretations are common, especially with the presence of fetal head molding and caput succedaneum [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of this study are its prospective nature and the use of pelvic floor ultrasound in transperineally approach. It is known that pregnant women find the transperineal ultrasound more comfortable than digital examination (23). This approach may become more common in the research settings, and therefore should be studied more extensively.…”
Section: Discussionmentioning
confidence: 99%
“…However, vaginal examination has several limitations, in-DOI: 10.1159/000507549 cluding operator dependence with significant inter-and intraobserver variability [1,2]. In addition, repeated vaginal examinations can increase the risk of chorioamnionitis [3][4][5][6][7] and can cause significant discomfort [8,9].…”
Section: Introductionmentioning
confidence: 99%